Bangladesh : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper and Statistical Appendix examines Bangladesh's nonfinancial state-owned enterprises. The paper argues that, given the overall policy environment and external vulnerabilities, the usefulness of the fixed exchange rate system in Bangladesh has run its course. Greater exchange rate flexibility is needed to ensure that the exchange rate sends appropriate market signals, and to enhance the authorities' ability to address more effectively and timely both domestic imbalances and external real shocks arising from a rapidly changing global environment. The paper also outlines the structure and recent performance of the commercial banking sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet